The favored language learning strategies of Islamic university EFL learners - Alfian Alfian (Universitas Syiah Kuala, 2021)
Despite the existence of many studies about language learning strategies (LLS) around the world, little work has been reported on the LLS use of Islamic university students from a qualitative perspective. Thus, to fill this empirical gap, this study is aimed to explore the LLS use and choice by learners studying at an Islamic university in Indonesia. This study employed a qualitative approach by interviewing 18 learners who would become teachers of English as a Foreign Language (EFL). They have been interviewed about the ways or strategies when they are learning English. The data gained from the interviews were analyzed by thematic analysis. The findings demonstrated that learners reported using the strategies which are classified into six LLS categories (memory, cognitive, compensation, metacognitive, affective, and social strategies) in learning English. However, most strategies reported by the learners were categorized into metacognitive strategies. Another significant finding is that several strategies such as practicing strategies (practicing four language skills; listening, speaking, reading, and writing), watching TV/ English Movies, memorizing, and using the internet were mostly reported by learners in improving their English skills. This study is beneficial for the classroom practice of teachers in enhancing their teaching methodology by knowing learners’ learning strategies to make it easier for the teachers to design the learning activities. Furthermore, this study is also beneficial for novice EFL learners in which the strategies in this study could be models for them.